Antioxidant, Antidiabetic, and Anti-obesity Potential of Ipomoea reptans Poir Leaves - Hendrik Kurniawan; Ermenilda Sonia Dacamis; Adelina Simamora; Priscilla Sari Dianauli Lumban Tobing; Ali Hanapiah; Adit Widodo Santoso (Borneo Journal of Pharmacy, 2020)
Ipomoea reptans Poir or kangkung is a popular leafy vegetable, a favorite to people in Asian countries. However, limited information is available on their bioactivities. In the present study, the antioxidant, antidiabetic, and anti-obesity potential of I. reptans leaves were investigated. Different fractions (ethanol, ethyl acetate, and hexane) of I. reptans leaves were evaluated for their scavenging activity on DPPH radicals, whereas their reducing potential was investigated by cupric reducing antioxidant capacity (CuPRAC), total antioxidant, and reducing power assays. The antidiabetic potential was investigated by their inhibition effect on α-glucosidase. Total phenolic and flavonoid contents of I. reptans leaves were solvent dependent. Ethyl acetate contained the highest phenolic content, followed by ethanol and hexane fractions. However, for flavonoid content, the order was ethanol > ethyl acetate > hexane. All fractions showed DPPH scavenging activity in a concentration-dependent manner, with activities weaker than standards ascorbic acid and BHT, in the order of ethanol > ethyl acetate > hexane. All fractions showed reducing capacity, but only hexane and ethanol fractions of I. reptans leaves showed inhibition on α-glucosidase, with hexane showed more potent inhibition compared to acarbose. The study also found that fractions of I. reptans inhibit lipase and trypsin, enzymes related to lipid metabolism. Findings in this study offer a prospect for I. reptans leaves as a functional food source for antioxidant, antidiabetic, and anti-obesity purposes.